The Relationship Between Natural Medicine Use and Recovery Time in Early Adult COVID-19 Patients - Natasya Cindy Edward; Meiyanti (Jurnal Multidisiplin Madani, 2023)
COVID-19 is a single-stranded RNA virus that infects through droplets. Drug consumption is one of the factors that affect the recovery of COVID-19 patients. The drug that has become a trend in the world is the use of natural ingredients, but people do not know whether it is effective in shortening the recovery time. Therefore, it is necessary to conduct research related to the relationship between the use of natural ingredients with the length of recovery of COVID-19 patients in early adulthood. This study used an analytical observational design with a cross-sectional method on 94 respondents in the Grogol Village area. Respondents fill out questionnaires via Google form and fill out questionnaires directly. Bivariate analysis of data using SPSS version 29. A total of 50 subjects consumed natural medicines (53.2%), namely jamu (58%), and 34 of them consumed almost every day (68%). There was no significant relationship between the use of natural medicine with the length of recovery of COVID-19 patients in early adulthood